Characterization of T cell immunophenotypes in intestinal transplantation: A pilot study - Guerra, Marjorie-Anne R. (Transpl Immunol, 2018)
Immunophenotyping of peripheral blood mononuclear cells has been shown to be a useful, non-invasive method of predicting acute cellular rejection (ACR) following intestinal transplantation (ITx). Our objectives were to characterize differences in the T cell immunophenotype of ITx recipients in peripheral blood samples (1) collected late versus early after ITx and (1) associated with episodes of ACR and infectious enteritis. An IRB-approved, cross-sectional study of ITx recipients was performed. Peripheral blood samples were collected during normal visits and episodes of allograft dysfunction. A total of 38 patients were included in the analysis: 31 ITx recipients (87% liver-inclusive allografts) and 7 intestinal failure control patients. Of the ITx patients, 26 patients were pediatric patients (< 21 years). A total of 70 samples were analyzed from ITx recipients, including 51 during normal visits and 19 during episodes of allograft dysfunction (median of 2 samples per patient; range of 1–6 samples per patient). In the late (n = 32) versus early post-ITx (n = 19) normal samples, there was a significantly higher percentage of central memory CD4 T cells (p = .001). In the ACR (n = 5) versus infectious enteritis (n = 14) samples, there was a higher percentage of CD8 T cells expressing HLA-DR (p = .002), CD57 (p < .001), and KLRG1 (p < .001) and a higher percentage of CD4 T cells expressing CD57 (p = .03). Additional studies are needed with larger cohorts to validate these changes in the T cell immunophenotype. Further elucidating T cell immunophenotypes in ITx will lead to a better understanding of immune mechanisms of allograft dysfunction, identification of potential biomarkers in ITx, and optimized selection of immunosuppressive therapies.